Large Dynamic Range Digital Nanodot Gradients of Biomolecules Made by Low‐Cost Nanocontact Printing for Cell Haptotaxis. Issue 19 (18th April 2013) - Ricoult, Sébastien G.; Pla‐Roca, Mateu; Safavieh, Roozbeh; Lopez‐Ayon, G. Monserratt; Grütter, Peter; Kennedy, Timothy E.; Juncker, David
Abstract A novel method is introduced for ultrahigh throughput and ultralow cost patterning of biomolecules with nanometer resolution and novel 2D digital nanodot gradients (DNGs) with mathematically defined slopes are created. The technique is based on lift‐off nanocontact printing while using high‐resolution photopolymer stamps that are rapidly produced at a low cost through double replication from Si originals. Printed patterns with 100 nm features are shown. DNGs with varying spacing between the dots and a record dynamic range of 4400 are produced; 64 unique DNGs, each with hundreds of thousands of dots, are inked and printed in 5.5 min. The adhesive response and haptotaxis of C2C12 myoblast cells on DNGs demonstrated their biofunctionality. The great flexibility in pattern design, the massive parallel ability, the ultra low cost, and the extreme ease of polymer lift‐off nanocontact printing will facilitate its use for various biological and medical applications.